Teaching in Indian Higher Education: Six Principles for Improvement - Mandal, Sayantan (International Higher Education, 2018)
While traditional, information-oriented lectures have been the de-facto practice in Indian higher education institutions (HEIs), they are often not effective in imparting learning. There is a need to reform instruction in colleges and universities, focusing on effective teaching and learning methods. As a first step in that direction, a national study of selected public HEIs attempts to assess the current state of teaching by focusing on different teaching practices at the undergraduate and master’s (graduate) levels. The study reflects on issues and challenges and suggests six principles to help improve teaching in Indian college and universities. This is a synthesis of the research, based on empirical evidence.